Adaption and parallel evolution of human-isolated H5 avian influenza viruses. Issue 6 (June 2020) - He, Wan-Ting; Wang, Liang; Zhao, Yuhui; Wang, Ningning; Li, Gairu; Veit, Michael; Bi, Yuhai; Gao, George F.; Su, Shuo
Summary: Avian-to-human transmission of highly pathogenic avian influenza viruses (HPAIV) and their subsequent adaptation to humans are of great concern to public health. Surveillance and early warning of AIVs with the potential to infect humans and pandemic potential is crucial. In this study, we determined whether adaptive evolution occurred in human-isolated H5 viruses. We evaluated all available genomes of H5N1 and H5N6 avian influenza A virus. Firstly, we systematically identified several new mutations in H5 AIV that might be associated with human adaptation using a combination of novel comparative phylogenetic methods and structural analysis. Some changes are the result of parallel evolution, further demonstrating their importance. In total, we identified 102 adaptive evolution sites in eight genes. Some residues had been previously identified, such as 227 in HA and 627 in PB2, while others have not been reported so far. Ten sites from four genes evolved in parallel but no obvious positive selection was detected. Our study suggests that during infection of humans, H5 viruses evolved to adapt to their new host environment and that the sites of adaptive/parallel evolution might play a role in crossing the species barrier and are the response to new selection pressure. The results provide insight to implement early detection systems for transitional stages in H5 AIV evolution before its potential adaptation for humans. Author summary line The prerequisite of surveillance and early warning of avian influenza viruses with the potential to infect humans depends on the identification of human-adaptation related mutations. In this study, we used a novel approach combining both phylogenetic and structural analysis to identify possible human-adaptation related mutations in H5 AIVs. Previous studies reported human-adaptation related mutations and some novel mutations exhibiting parallel evolution. Our result provides new insights into how AIVs adapt to humans by point mutations.